Rethinking the Drug Distribution and Medication Management Model: How a New York City Hospital Pharmacy Department Responded to COVID‐19. Issue 8 (9th September 2020) - Dzierba, Amy L.; Pedone, Trisha; Patel, Mona K.; Ciolek, Alana; Mehta, Monica; Berger, Karen; Ramos, Liz G.; Patel, Viha D.; Littlefield, Audrey; Chuich, Taylor; May, Hetal B.; Muir, Justin; et al.
Abstract: Beginning in March 2020, New York City began the fight against coronavirus disease 2019. Health care workers were faced with a disease that led to significant morbidity and mortality with no proven therapies. As hospitals became inundated with patients and underwent rapid expansion of capacity, resources such as drugs, protective and medical equipment, and hospital staff became limited. Pharmacists played a critical role in the management of clinical care and drug delivery during the pandemic. As members of the department of pharmacy within NewYork‐Presbyterian Hospital, we describe our experiences and processes to overcome challenges faced during the pandemic. Strict inventory management through the use of daily usage reports, frequent communication, and minimization of waste was critical for the management of drug shortages. The creation of guidelines, protocols, and restrictions were not only used to mitigate drug shortages, but also helped educate health care providers and guided medication use. Managing technology through setting up new automatic dispensing cabinets to address hospital expansions and modifying the electronic order entry system to include new protocols and drug shortage information were also vital. Additional key pharmacist functions included provision of investigational drug service support and training of pharmacists, prescribers, nurses, and respiratory therapists to educate and standardize medication use. Through implementation of operational and clinical processes, pharmacists managed critical drug inventory and guided patient treatment. As the pandemic continues, pharmacists will remain vital members of the multidisciplinary team dedicated to the fight against the virus.